Increasing Prescription Opioid and Heroin Overdose Mortality in the United States, 1999–2014: An Age–Period–Cohort Analysis - Huang, Xiwen; Keyes, Katherine M.; Li, Guohua (American journal of public health (1971), 2018)
Objectives. To assess cohort effects in prescription opioid and heroin overdose mortality in the United States. Methods. Using the National Center for Health Statistics’ multiple-cause-of-death file for 1999 to 2014, we performed an age–period–cohort analysis of drug overdose mortality in the United States. Results. Compared with those born in 1977 and 1978, individuals born between 1947 and 1964 experienced excess risks of prescription opioid overdose death (e.g., for the 1955–1956 birth cohort, rate ratio [RR] = 1.27; 95% confidence interval [CI] = 1.09, 1.48) and of heroin overdose death (e.g., for the 1953–1954 birth cohort, RR = 1.32; 95% CI = 1.11, 1.57). Those born between 1979 and 1992 also experienced an increased risk of heroin overdose death (e.g., for the 1989–1990 birth cohort, RR = 1.23; 95% CI = 1.01, 1.50). The cohort effects were consistent between sexes. Conclusions. Individuals born between 1947 and 1964 and between 1979 and 1992 are particularly afflicted by the opioid epidemic. Intervention programs are needed to reduce the excess overdose mortality in these specific demographic groups.